3D printing of cellular materials for advanced electrochemical energy storage and conversion. Issue 14 (25th March 2020) - Tian, Xiaocong; Zhou, Kun
Abstract : This article provides a comprehensive overview of 3D-printed cellular materials for advanced electrochemical energy storage and conversion applications. Abstract : 3D printing, an advanced layer-by-layer assembly technology, is an ideal platform for building architectures with customized geometries and controllable microstructures. Bio-inspired cellular material is one of most representative 3D-printed architectures, and attracting growing attention compared to block counterparts. The integration of 3D printing and cellular materials offer massive advantages and opens up great opportunities in diverse application fields, particularly in electrochemical energy storage and conversion (EESC). This article gives a comprehensive overview of 3D-printed cellular materials for advanced EESC. It begins with an introduction of advanced 3D printing techniques for cellular material fabrication, followed by the corresponding material design principles. Recent advances in 3D-printed cellular materials for EESC applications, including rechargeable batteries, supercapacitors and electrocatalysts are then summarized and discussed. Finally, current trends and challenges along with in-depth future perspectives are provided.